A fragment of Calpain-1 cleaved α-Synuclein quantified in serum is upregulated in patients with Parkinson’s disease - Signe Holm Nielsen; Cecilie Møller Hausgaard; Meryem Benmarce; Morten Karsdal; Kim Henriksen (Scientific Reports)
Abstract Parkinson’s disease (PD) is a progressive neurodegenerative condition. One of the unmet medical needs in PD, are tools for better diagnosis, prognosis, and efficacy of treatment, which reflects the disease course of the individual patient. Alpha-Synuclein (α-Synuclein) is a hallmark of synucleinopathies such as PD, where α-Synuclein aggregates are deposited. Calpain-1 is an enzyme, located in the presynaptic terminal, and shown to be active as an early event related to aggregation of α-Synuclein. The aim of this study was to develop and evaluate a competitive ELISA, targeting a Calpain-1 specific cleavage site of α-Synuclein, named α-Syn-C, and evaluate it in serum from patients diagnosed with PD and comparing to healthy matched donors. A monoclonal antibody was raised against the α-Synuclein fragment generated by cleavage of Calpain-1 and employed in an ELISA assay. The assay was developed, technically evaluated, and quantified in two independent cohorts of patients diagnosed with PD and compared to the healthy donors. The discovery cohort showed α-Syn-C was significantly upregulated in patients with PD compared to healthy donors (p =0.0007), with a diagnostic value of AUC = 0.83. The evaluation cohort showed similar results with an ability to differentiate PD patients from healthy donors (p < 0.0001) with an AUC = 0.85. These findings are exploratory and hypothesis generating, indicating the α-Syn-C biomarker may be useful in managing PD patients, and needs to be validated in larger cohorts and longitudinal studies.